Hamartoma-like lesions in the mouse retina: an animal model of Pten hamartoma tumour syndrome - Nobuhiko Tachibana; Yacine Touahri; Rajiv Dixit; Luke Ajay David; Lata Adnani; Robert Cantrup; Tooka Aavani; Rachel O. Wong; Cairine Logan; Kyle C. Kurek; Carol Schuurmans (The Company of Biologists, 2018)
PTEN hamartoma tumour syndrome (PHTS) is a heterogeneous group of rare, autosomal dominant disorders associated with PTEN germline mutations. PHTS patients routinely develop hamartomas, which are benign tissue overgrowths comprised of disorganized 'normal' cells. Efforts to generate PHTS animal models have been largely unsuccessful due to the early lethality of homozygous germline mutations in Pten, together with the lack of hamartoma formation in most conditional mutants generated to date. We report herein a novel PHTS mouse model that reproducibly forms hamartoma-like lesions in the central retina by postnatal day 21. Specifically, we generated a Pten conditional knockout (cKO) using a retinal-specific Pax6::Cre driver that leads to a nearly complete deletion of Pten in the peripheral retina but produces a mosaic of 'wild-type' and Pten cKO cells centrally. Structural defects were only observed in the mosaic central retina, including in Müller glia and in the outer and inner limiting membranes, suggesting that defective mechanical integrity partly underlies the hamartoma-like pathology. Finally, we used this newly developed model to test whether rapamycin, an mTOR inhibitor that is currently the only PHTS therapy, can block hamartoma growth. When administered in the early postnatal period, prior to hamartoma formation, rapamycin reduces hamartoma size, but also induces new morphological abnormalities in the Pten cKO retinal periphery. In contrast, administration of rapamycin after hamartoma initiation fails to reduce lesion size. We have thus generated and used an animal model of retinal PHTS to show that, although current therapies can reduce hamartoma formation, they might also induce new retinal dysmorphologies. This article has an associated First Person interview with the first author of the paper.